IMPROVING THE COLLEGE STUDENTS’ SPEAKING SKILL OF POTENSI UTAMA UNIVERSITY THROUGH TOTAL PHYSICAL RESPONSE METHOD - Dwi Suci Amaniarsih; Firdayanti Firdaus (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2019)
Abstract The purpose of this study is to find out how the application of the Total Physical Response method in an effort to improve English language skill. The subjects in this study were the college students of Potensi Utama University in Medan. While the object of this research is the application of the TPR method, to improve students' skill to speak English. Based on the results of the study it can be seen that the percentage of the results of the completeness of the students' scores between the preliminary conditions and the first and the second cycle has increased. In the preliminary conditions the percentage of completeness in student grades is only 24%. In the first cycle, the percentage of completeness of students' scores increased to 40%, while in the second cycle there was a significant increase to 68%. If a comparison is made between students 'speaking abilities during the preliminary conditions and after the application of the TPR method, there is a 53% increase in students' English speaking skill using the TPR method. Thus it can be said that the use of the TPR method can improve students' English skill in the procedure text. Keywords: Speaking skill, Total Physical Response method